Third space professionals and academic collaboration to embed mental wellbeing in the curriculum - Zoë Allman; Rachel Davies (Journal of Learning Development in Higher Education)
Collaboration between third space professionals and academics has facilitated the effective implementation of embedded mental wellbeing in the curriculum at a UK university. De Montfort University in Leicester aimed to achieve a whole provider approach to embedding mental wellbeing, bringing expertise, skills and knowledge from third space professionals and academics to the task.